From Fitness Tracking to Augmented Shopping Experience: Perceptions and Use of Mobile Payment among Runners Using Wearable Devices - Özlem Özdinç (Selcuk University, 2021)
Regularly exercising users of sports wearables (e.g., smartwatches) comprise an overlooked group in the literature on mobile payment despite their frequent use of such high-tech devices that allow making mobile payments. Payment-capable wearables could lead to a more health-conscious shopping experience through push notifications that make customised suggestions-say, for fluid/food intake based on dehydration/calories burnt, since they track exercise (e.g., steps), health (e.g., pulse), and well-being data (e.g., sleep cycles). Accordingly, this study aims to explore the perceptions and use of mobile payment technology among a sample of runners, who track their exercise metrics using sports wearables. A typical runner that we captured data from was an educated, employed, and adult female user of high-tech sports wearables, who makes nearly 9 kilometres on each of her four runs in a week, but taps her smartphone-not her wearable-to make payments for necessity goods (e.g., food, apparel) and services (e.g., bills, bookings) through either Alipay or Apple Pay. Mobile payment was among the top three preferred methods of payments; however, only 4% were using their wearable device for that purpose. Runners' had a positive perception of the mobile payment technology, which was homogeneous across the categories of their socio-demographic characteristics and exercise metrics. These results indicate that mobile payment use on a smartphone is common among the physically active, but the convergence of that technology with high-tech wearable devices is yet to find acceptance.